Adrenal Disorders in Pregnancy. A Comprehensive Review and Prospects for Future Research - Kinga Filipek; Natalia Zalewska; Bartosz Skiekowski; Waldemar Mugała; Sebastian Mrugała; Michał Muciek; Jakub Kawka; Filip Czyżewski; Katarzyna Baranowska; Alicja Baranowska (Kazimierz Wielki University, 2024)
Introduction and purpose: Adrenal disorders cover a spectrum of conditions, including adrenal insufficiency, Cushing's syndrome and others. Each disorder has its own implications for pregnancy and requires an individualised approach. This review aims to provide a comprehensive overview of adrenal disorders during pregnancy, such as endogenous Cushing's syndrome, adrenal insufficiency, primary aldosteronism, and pheochromocytoma. Brief description of the state of knowledge: During pregnancy, a number of adaptive processes take place in a woman's body including changes in the endocrine system. Given all these changes, adrenal diseases pose both diagnostic and therapeutic challenges. The symptoms of adrenal diseases often overlap with those observed during physiological pregnancy. Adrenal disorders during pregnancy if unrecognised or treated inadequately, can lead to negative consequences for the mother and foetus, indicating the importance of awareness of these conditions among physicians.  Conclusions: Treating and diagnosing adrenal diseases during pregnancy is a major challenge for doctors. It is crucial to diagnose adrenal diseases in pregnant women as early as possible, and to meticulously plan pregnancies for women diagnosed before conception to prevent the negative consequences of untreated adrenal disorders. Optimal control of treatment before conception should be sought. Access to specialised centres with multidisciplinary teams experienced in treating these conditions is crucial for optimal maternal and foetal care.